2016
DOI: 10.15825/1995-1191-2015-4-90-94
|View full text |Cite
|
Sign up to set email alerts
|

St2 in Rejection of the Transplanted Heart

Abstract: 1 ФГБУ «Федеральный научный центр трансплантологии и искусственных органов имени академика В.И. Шумакова» Минздрава России, Москва, Российская Федерация 2 ГБОУ ВПО «Первый Московский государственный медицинский университет имени И.М. Сеченова» Минздрава России, Москва, Российская Федерация 3 ГБОУ ВПО «Российский национальный исследовательский медицинский университет имени Н.И. Пирогова» Минздрава России, кафедра кардиологии, Москва, Российская Федерация Обзор литературы посвящен анализу прогностической роли би… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The results of this analysis will be especially in demand now, when historians have clearly increased their interest in studying the features of education in various regions of the Russian Empire Cherkasov et al, 2019a;Magsumov et al, 2018;Shevchenko et al, 2016). This year, the first post-Soviet article was published that claimed to analyze the evolution of the primary education system in Cossack regions (Molchanova et al, 2019).…”
Section: Introductionmentioning
confidence: 97%
“…The results of this analysis will be especially in demand now, when historians have clearly increased their interest in studying the features of education in various regions of the Russian Empire Cherkasov et al, 2019a;Magsumov et al, 2018;Shevchenko et al, 2016). This year, the first post-Soviet article was published that claimed to analyze the evolution of the primary education system in Cossack regions (Molchanova et al, 2019).…”
Section: Introductionmentioning
confidence: 97%
“…For example, A.A. Cherkasov convincingly showed that by 1914, in the Russian Empire, 80 % of school-aged children had received education at public or private schools or at home (Cherkasov, 2011: 146-147). Meanwhile, it is becoming increasingly obvious that education in the great power was region-specific to a sufficient extent to explore the history of education separately in different regions (Khramtsov, 2018;Shevchenko et al, 2016). The Don Host Oblast was not an exception in this aspect, but works devoted to the education in the area are mixed and inconsistent.…”
Section: Introductionmentioning
confidence: 99%